Effect of Crataegus Azarolus Extracted in Treatment of Giardia Lamblia Infection (Indian Journal of Forensic Medicine & Toxicology, 2021)
The infection of Giardia lamblia has a universal distribution and it is a major cause of diarrhea conditionin adults and children and is transmitted by route of fecal-oral through direct or indirect cysts ingestion. 20adult male rats were used and distributed to the following groups (5 rats in each group); negative group: ratsreceived distill water, positive group: infected rats with G. lamblia at dose 103 cyst/ml. third group infectedwith G. lamblia and treated by 150mg/kg of C. azarolus extract for six weeks. Fourth group: infectedwith G. lamblia and treated by 250mg/kg of C. azarolus extract for six weeks. The results demonstratedsignificant (P < 0.05) increased in levels of malondialdehyde (MDA) immunoglobulin (Ig) A, IgG andIgM with significant (P < 0.05) decreased in levels of glutathione (GSH) in an infected group comparedwith control group. The findings of treated groups demonstrated non-significant (P < 0.05) difference in allstudied parameters compare with control group when using C. azarolus extract. It was concluded that C.azarolus extract has been role against the G. lamblia.
Keywords: G. lamblia, C. azarolus extract; Immunoglobulin